Large-Scale Development of Antibacterial Scaffolds: Gentamicin Sulfate-Loaded Biodegradable Nanofibers for Gastrointestinal Applications - Klicova, Marketa; Mullerova, Senta; Rosendorf, Jachym; Klapstova, Andrea; Jirkovec, Radek; Erben, Jakub; Petrzilkova, Michaela; Raabová, Hedvika; Šatínský, Dalibor; Melicherikova, Jana; Palek, Richard; Liska, Vaclav; et al. (ACS omega, 2023)
The ever-increasing demands of modern medicine drive the development of novel drug delivery materials. In particular, nanofibers are promising for such materials due to their favorable properties. However, most development is still carried out through laboratory techniques that do not allow extensive and reproducible characterization of materials, which slows medical research. In this work, we focus on the large-scale fabrication and testing of specific antibacterial nanofibrous materials to prevent the postoperative complications associated with the occurrence of bacterial infection. Poly-ε-caprolactone with gentamicin sulfate (antibiotic) in different concentrations was electrospun via a needleless device. The amount of antibiotics was proven by elemental analysis, UV spectrophotometry, and HPLC. The cytocompatibility of the materials was verified in vitro according to ISO 10993-5. The cell adhesion and proliferation were assessed after 2, 7, 14, and 21 days using the CCK-8 metabolic assay, fluorescence, and scanning electron microscopy. The tested nanofiber materials supported cell growth. Antibacterial tests were performed to confirm the release of gentamicin sulfate, and its antibacterial properties were proven toward Staphylococcus gallinarum and Escherichia coli bacteria. The effect of ethylene oxide sterilization was also studied. The sterilized nanofibrous layers are cytocompatible while antibacterial and therefore suitable for medical applications.